Influence of Gastrectomy on Cortical and Cancellous Bones in Rats - Jun Iwamoto; Yoshihiro Sato; Hideo Matsumoto (Gastroenterology Research and Practice)
The aim of the present study was to examine the influence of gastrectomy (GX) on cortical and cancellous bones in rats. Twenty male Sprague-Dawley rats were randomized into the two groups of 10 animals each: a sham operation (control) group and a GX group. Seven weeks after surgery, the bone mineral content and density (BMC and BMD, resp.) and the mechanical strength of the femur were determined, and bone histomorphometric analyses were performed on the tibia. GX induced decreases in the BMC, BMD, ultimate force, work to failure, and stiffness of the femoral distal metaphysis and the BMC, BMD, and ultimate force of the femoral diaphysis. GX induced a decrease in cancellous bone mass, characterized by an increased osteoid thickness, osteoid surface, osteoid volume, and bone formation. GX also induced a decrease in cortical bone mass, characterized by increased endocortical bone resorption. The GX induced reductions in the bone mass and strength parameters were greater in cancellous bone than in cortical bone. The present study showed that the response of bone formation, resorption, and osteoid parameters to GX and the degree of GX-induced osteopenia and the deterioration of bone strength appeared to differ between cortical and cancellous bones in rats.